Leadership practices and principles of a malay- muslim chief executive officer at a selected Malaysian government-linked company - Haron, Khalidah (2014)
The purpose of the study is to investigate the lived experience of a Malay Chief Executive Officer (CEO) who has demonstrated effective performance in a Government Link Company (GLC), with the intention of revealing his underlying leadership principles as a strategic leader. As a CEO, his leadership was not limited to only realizing the aims of organizational leadership aspect in general, but it was also about him as an individual, it was about his principles and values that he upholds based upon a firm and reliable foundation. This study was guided by three research questions:(1) What are the CEO’s guiding principles that became the foundation of his values and leadership practices, (2) How does being a Muslim, shape this CEO leadership principles and practices, (3) Who or what specific phenomenon gives the greatest impact in shaping this CEO’s principles. This study provided a better understanding of how being Muslim, Islamic teachings have implication on his principles and leadership practices. Why Islamic teachings? According to Malaysian constitution Article 160, Malays as Malaysian citizen, are Muslims. Malay is a race, a race not only distinct because of its culture but a need to adhere to the religious code of Islam. In Islam, the oneness of Allah “Tawheed”, is the underpinning factor that binds and infuses the inner meaning and values of Muslims. The organizational leadership research framework referred to in this study, was Kriger’s and Seng’s (2005) proposed expended model to Yukl’s multiple linkage contingency model which includes the spirituality imputes as variables, and the research approach adopted was a biographical narrative qualitative approach. Series of semi structured qualitative interviewing interviews, documentary analysis, and literature review were used to explore the life experiences of this Malay, Muslim CEO, and in addition to that, several non-participant observations data were gathered by the researcher through various formal and informal occasions encountered with the CEO. Being an insider and a member of this GLC management team, the researcher further utilized own personal experiences to make sense of the lived experience of this CEO. Issues of trustworthiness, in terms of credibility, transferability, dependability, and confirmability were addressed by adopting; data triangulation, non-participation observation check, methodological and theory triangulation. The outcome of this study suggests that the development of one’s leadership principles is the outcome of one’s own personal leadership philosophy which is shaped by personal life experiences under five major themes; inherent talent; leadership development out of struggle and hardship; developed for a cause that is worthy of strong commitment; developed for a process of learning from experience, such as personal mistakes or failures, influence of positive or negative role; and religious upbringing which includes his belief systems as being an integrative system of the organizational leadership. This study contributes to the continuing discussion on leadership with inner meaning through describing the experiences of this Malay CEO moving through different stages of his life, his career and exploring the contingency theory of leadership based on his religion, Islam. The in-depth, semi-structured qualitative interviewing approach, offers a fuller appreciation of the challenges and opportunities involved, demystifying (make difficult subject clear and easy to understand) the leadership major challenges faced by organizational leaders today with regards to the enactment of leadership with deep inner meaning. The study too, has provided valuable information that may benefit others in the leadership position in navigating their leadership construct. Simply stated, the question of whether leadership is just based on organizational leadership theories which over emphasis on “observables’ construct; (1) “having”: having the right skills, competencies, resources or personality traits appropriate to the task, or (2) “doing”: behaving or expressing activities, a situational leadership of one sort or another, to new paradigm of not only emphasizing on just observables construct of (1) “having”, (2) “doing”, but also (3) “being”. Leadership is not primarily a question of having the right traits, competencies and behaviors for the situation, but a question of “being”. Construct of “being” is being human, and as human being, one need to act out of and being in touch with the source of meaning, on how to lead an organization where the organizational members are seeking ways to live it through to their inner individual values.